Properties of Fixed Point Sets of Monotone Nonexpansive Mappings in Banach Spaces. (3rd March 2016) - Bachar, Mostafa; Khamsi, Mohamed A.
ABSTRACT: In this work, we discuss the properties of the common fixed points set of a commuting family of monotone nonexpansive mappings. In particular, we show that under suitable assumptions, this set is a monotone nonexpansive retract.